Achieving carbon efficient transport : backcasting from London - Hickman, R; Ashiru, O; Banister, D (Transportation Research Board of the National Academies, 2009)
Transportation is a major user of carbon-based fuels and is increasingly being highlighted as the sector that contributes the least to carbon dioxide (CO2) emission reduction targets. This paper reports on the findings of the current Visioning and Backcasting for Transport in London study, which considers the role of the transportation sector in reducing CO2 emissions in London. A backcasting study approach was used and the likely impacts of alternative images of 2025 were tested. A transportation and carbon simulation game was also developed for London. Within this game, users are able to consider a series of potential policy packages, such as low-emission vehicles, alternative fuels, pricing regimens, public transportation, walking and cycling, strategic and local urban planning, information and communication technologies, smarter choices, ecological driving and slower speeds, long-distance travel substitution, freight transportation and international air and select various levels of application to help achieve headline CO2 emissions reduction targets. The roles of two external enabling measures, carbon rationing and oil pricing, were also considered. The paper considers an optimized policy package for 2025. A deep reduction in CO2 emissions from the transportation sector is theoretically possible, yet difficult to achieve. The main perceived problem is in engendering an interest in the public to change consumer purchases and behaviors. The huge challenge now is to map out and discuss a variety of policy pathways to carbon efficiency in the transportation sector and then to enable and achieve a level of consumer and behavioral change consistent with strategic aspiration.